OPTIMALISASI KINERJA PERAWAT MELALUI MAKP MODEL TIM DI RSU SUNDARI MEDAN - Fazar Amanah Ariga; Youlanda Sari; Nurul Haflah; Suherni (Jurnal Pengabdian Keperawatan Dan Kesehatan Holistik, 2026)
Nurse performance affects the quality of hospital services. The Professional Nursing Care Method (MAKP) team model emphasizes teamwork, clear task division, and professional responsibility. This community service aims to optimize nurse performance through the implementation of the MAKP team model at RSU Sundari Medan, involving 15 nurse respondents. The activities were conducted through education, training, and mentoring, with evaluation using observation and interviews. The results showed improvements in nurses’ understanding, teamwork, professional responsibility, and performance in delivering nursing care. The MAKP team model also enhanced service quality, documentation, and team communication. Sustainability requires management support, regular training, and periodic evaluation.